Dental students' reports of occupational exposures to potentially infectious biological material in a Brazilian School of Dentistry - Camila Pinelli; Sabrina do Nascimento Neri; Leonor de Castro Monteiro Loffredo (Instituto de Estudos em Saúde Coletiva da Universidade Federal do Rio de Janeiro, 2016)
Abstract Introduction Occupational exposures to contaminated biological material in dental teaching settings can place students at higher risk of bloodborne infections. Methods This cross sectional study was conducted using a self-administered questionnaire culturally adapted to Portuguese language, Brazil. In total, 173 undergraduate dental students agreed to participate in the study, answered the questionnaire, and filled in the details about their own occupational exposures. The association of these factors was analyzed by the chi-square test or Fisher's exact test using Stata® software. Results High prevalence of occupational exposures (40%) was observed among the participants, and 52% of the accidents were not reported to the clinical instructor. The most frequent type of accident was related to "puncture/cut/abrasion" (56%). Significant correlation was observed between number of exposures and academic year (p=0.002), age (p=0.012), gender (p=0.010), and between number of injuries in the last 6 months and academic year (p=0.003). No significant correlation was observed between number of exposures and dominant hand, use of protective eyewear or Hepatitis B vaccination status (p>0.05). Conclusion Additional teaching strategies need to be developed to motivate adherence to occupational post-exposure protocols regarding biological material, improving the notification of the occupational exposures that occur among dental students.